Vietnamese Parents and Czech Nannies: Second-Generation Immigrant Children and their Educators - Souralová, Adéla (Journal of Education Culture and Society, 2020)
Many second-generation Vietnamese immigrant children in the Czech Republic are brought up by Czech nannies. While their parents are incorporated into the labour market in order to provide their children with suffi cient economic capital for their education, the role of caregivers is relinquished to nannies. Both parents and nannies become important actors in the children’s educational process, from the stage of acquiring fi rst words, through primary school, to the moment they are admitted into university. This paper analyses the roles of parents and nannies in this educational process. It draws upon 60 interviews conducted with fi rst-generation immigrant mothers, second-generation immigrants, and Czech nannies. The perspective of all three actors are presented here in order to reveal the interviewee’s understanding of the role of education in the parent-child and nanny-child relationships. How is education manifested in the defi nitions of parenting and caregiving? The paper illuminates the educational strategies taking place outside the educational institution as being an inherent part of everyday life. Simultaneously, the article reveals the meanings of education for the immigrant families as being linked both to past experience and future expectations.